"A Toxic Trend?": Generational Conflict and Connectivity in Twitter Discourse Under the #BoomerRemover Hashtag. (7th November 2020) - Sipocz, Daniel; Freeman, Jessica D; Elton, Jessica
Abstract: Background and Objectives: This study examines the #BoomerRemover hashtag on Twitter to understand discourses of intergenerational conflict and unity that emerged during the novel coronavirus disease 2019 global pandemic. The research highlights conflict and connection surrounding generational cohorts via social media, particularly in a time of crisis. Research Design and Methods: The study used an inductive-dominant qualitative content analysis to examine 536 tweets collected between March 9 and April 9, 2020 under #BoomerRemover. Results: Data analysis revealed five forms of conflictive generational discourse: derogatory endorsement of the #BoomerRemover moniker, conflict regarding the nature and origins of the moniker, conflict surrounding the virus, political conflict, and generational jabs. Two forms of intergenerationally unifying discourse were identified: implicit and explicit pleas for connectivity. Discussion and Implications: The analysis of discourse under #BoomerRemover revealed more nuanced expressions surrounding generational cohorts than widely reported in media outlets. Some users tweeted the hashtag in ways that reflected conflict, with #BoomerRemover acting as a vector through which stereotypes were perpetuated and magnified. However, a number of users tweeted the hashtag to call for intergenerational connectivity, highlighting the complexity of online discourse. These results yield implications for the study of online generational discourse, particularly in light of the unique circumstances surrounding the pandemic.